Globalization and the Human Factor in the Public Service Organization - Argyriades, Demetrios (Mercados y Negocios, 2022)
The assumption underpinning the push to “shrink the State” may have been that the ongoing globalization of markets had made traditional forms of government intervention in economic sphere redundant and possibly harmful; and that, in any event, markets were more efficient at allocating resources than either politicians or the professional bureaucrats. In my modest opinion, this view though not completely unfounded, takes insufficient cognizance of a subtle, multiple shift which, since the 1980s, has drastically altered the balance of power world-wide: from the South and from the East to the Northwest; from the public sector to private enterprise; and in a number of countries, from organized labour to management. The dominant ideology during the 1980s and 1990s reflected this state of affairs and continues in the 21st Century.